Development of Knowledge-Attitude-Practice Questionnaire on Oral Nutrition Supplement Among Nurses in Oncology Department and its Reliability and Validity Test (Global Journal of Medical Research, 2023)
Objective To develop a questionnaire on oncology nurses knowledge-attitude-practice towards oral nutrition supplementation and to test its reliability and validity Methods Based on literature review and Delphi expert correspondence the initial questionnaire was constructed on the basis of knowledge-attitude-practice mode A total of 265 oncology nurses from 5 tertiary care hospitals in Jiangsu Province were selected by convenience sampling method for pre-survey to test the reliability and validity of the questionnaire and form the final version Results The questionnaire included three dimensions knowledge attitude and practice with a total of 43 items exploratory factor analysis extracted a total of five common factors with a cumulative variance contribution rate of 81 087 confirmatory factor analysis results showed that the model fitted well
Keywords: nurses; oral nutritional supplements; knowledge-attitude-practice; reliability; validity